Monitoring Early Fusion Dynamics of Human Immunodeficiency Virus Type 1 at Single-Molecule Resolution - Dobrowsky, Terrence M. (American Society for Microbiology (ASM), 2008)
The fusion of human immunodeficiency virus type 1 (HIV-1) to host cells is a dynamic process governed by the interaction between glycoproteins on the viral envelope and the major receptor, CD4, and coreceptor on the surface of the cell. How these receptors organize at the virion-cell interface to promote a fusion-competent site is not well understood. Using single-molecule force spectroscopy, we map the tensile strengths, lifetimes, and energy barriers of individual intermolecular bonds between CCR5-tropic HIV-1 gp120 and its receptors CD4 and CCR5 or CXCR4 as a function of the interaction time with the cell. According to the Bell model, at short times of contact between cell and virion, the gp120-CD4 bond is able to withstand forces up to 35 pN and has an initial lifetime of 0.27 s and an intermolecular length of interaction of 0.34 nm. The initial bond also has an energy barrier of 6.7 k(B)T (where k(B) is Boltzmann's constant and T is absolute temperature). However, within 0.3 s, individual gp120-CD4 bonds undergo rapid destabilization accompanied by a shortened lifetime and a lowered tensile strength. This destabilization is significantly enhanced by the coreceptor CCR5, not by CXCR4 or fusion inhibitors, which suggests that it is directly related to a conformational change in the gp120-CD4 bond. These measurements highlight the instability and low tensile strength of gp120-receptor bonds, uncover a synergistic role for CCR5 in the progression of the gp120-CD4 bond, and suggest that the cell-virus adhesion complex is functionally arranged about a long-lived gp120-coreceptor bond.